1988
DOI: 10.1007/bf00130931
|View full text |Cite
|
Sign up to set email alerts
|

The chemical fractionation of atmospheric aerosol as a result of snow crystal formation and growth

Abstract: The relationships between the physical and chemical properties of mixed-phase clouds were investigated at Storm Peak Laboratory (3220m MSL) located near the continental divide in northwestern Colorado. Interstitial aerosol particles, cloud droplets and snow crystals were concurrently collected when the laboratory was enveloped by a precipitating cloud. All samples were analyzed for trace elements, soluble anions, electrical conductivity and acidity.The results show average trace constituent concentration ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…This occurs either by collision of liquid droplets with ice particles followed by shock freezing (timing process) for large enough ice crystals or by diffusion of water vapor to the ice because of the lower vapor pressure of ice with respect to water (Wegener-Bergeron-Findeisen mechanism [Pruppacher and Klett, 1997]). Borys et al [1988] demonstrated that nucleation of cloud droplets followed by ice crystal r'mm•g is the main process in taking up aerosols in mixed clouds, the collision of ice particles with interstitial aerosols re,naming an inefficient process (Figure 1). During the freezing of supercooled liquid droplets, solutes present as salts will be segregated by the ice leading to an hfi•omogeneous distribution in the formed ice particle, but the bulk chemistry of rimed droplets will not differ from that of supercooled droplets.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs either by collision of liquid droplets with ice particles followed by shock freezing (timing process) for large enough ice crystals or by diffusion of water vapor to the ice because of the lower vapor pressure of ice with respect to water (Wegener-Bergeron-Findeisen mechanism [Pruppacher and Klett, 1997]). Borys et al [1988] demonstrated that nucleation of cloud droplets followed by ice crystal r'mm•g is the main process in taking up aerosols in mixed clouds, the collision of ice particles with interstitial aerosols re,naming an inefficient process (Figure 1). During the freezing of supercooled liquid droplets, solutes present as salts will be segregated by the ice leading to an hfi•omogeneous distribution in the formed ice particle, but the bulk chemistry of rimed droplets will not differ from that of supercooled droplets.…”
Section: Introductionmentioning
confidence: 99%
“…The riming process becomes efficient only if droplet diameter is larger than 10 µm and crystal diameter is greater than about 50, 150 and 300 μm, when considering dendrites, hexagonal plates and columns, respectively [29] [30]. Riming is likely to be common during the relatively warm summer season in coastal areas of Antarctica, whereas at the South Pole where temperatures are lower, riming is less likely, i.e.…”
Section: Physical and Chemical Processesmentioning
confidence: 99%
“…2. Gases may be absorbed into water drops and subsequently get incorporated into ice through the riming process [ Diehl et al , 1998; Borys et al , 1988; Mitchell and Lamb , 1989]. This process is included in the model cloud microphysical transformation.…”
Section: Regional Model Descriptionmentioning
confidence: 99%